Pharmacological modulation of mitochondrial calcium uniporter controls lung inflammation in cystic fibrosis - Rimessi, Alessandro (Sci Adv, 2020)
Mitochondria physically associate with the endoplasmic reticulum to coordinate interorganelle calcium transfer and regulate fundamental cellular processes, including inflammation. Deregulated endoplasmic reticulum–mitochondria cross-talk can occur in cystic fibrosis, contributing to hyperinflammation and disease progression. We demonstrate that Pseudomonas aeruginosa infection increases endoplasmic reticulum–mitochondria associations in cystic fibrosis bronchial cells by stabilizing VAPB-PTPIP51 (vesicle-associated membrane protein–associated protein B–protein tyrosine phosphatase interacting protein 51) tethers, affecting autophagy. Impaired autophagy induced mitochondrial unfolding protein response and NLRP3 inflammasome activation, contributing to hyperinflammation. The mechanism by which VAPB-PTPIP51 tethers regulate autophagy in cystic fibrosis involves calcium transfer via mitochondrial calcium uniporter. Mitochondrial calcium uniporter inhibition rectified autophagy and alleviated the inflammatory response in vitro and in vivo, resulting in a valid therapeutic strategy for cystic fibrosis pulmonary disease.